2008
DOI: 10.1007/s10641-008-9393-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the blind cavefish Phreatichthys andruzzii and Garra barreimiae within the family Cyprinidae

Abstract: The phylogenetic relationships of two cavefish, Phreatichthys andruzzii and Garra barreimiae, belonging to the family Cyprinidae, were investigated by sequencing the mitochondrial cytochrome b gene. These cavefish species are native to Somalia (eastern Africa) and Oman (southeastern Arabian peninsula), respectively, and so far no molecular support to their taxonomy and phylogenetic position was ever provided. The analysis of cytochrome b sequences showed that the species are monophyletic taxa, closely related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…G. barreimiae and G. rufa. With more taxonomic sampling than that of Colli et al (2009) where our sequence (full length Cyt b) of Phreatichthys was retrieved, our study showed that this genus is closely related to a clade of African and West Asian Garra species (Fig. 1).…”
Section: Subtribementioning
confidence: 86%
See 1 more Smart Citation
“…G. barreimiae and G. rufa. With more taxonomic sampling than that of Colli et al (2009) where our sequence (full length Cyt b) of Phreatichthys was retrieved, our study showed that this genus is closely related to a clade of African and West Asian Garra species (Fig. 1).…”
Section: Subtribementioning
confidence: 86%
“…Therefore, we propose that Phreatichthys should be treated as a junior synonym of Garra. Colli et al (2009) showed that Phreatichthys, which is endemic to Somalia, is most closely related to West Asian Garra, i.e. G. barreimiae and G. rufa.…”
Section: Subtribementioning
confidence: 99%
“…Using a Bayesian approach and the cytb as a marker, Colli et al (2008) found that divergence times at 95% highest posterior density interval were 8.3-11.5 Myr for the subclade including P. andruzzii and G. barreimiae and 0.8-2.0 Myr for the epigean and hypogean G. barreimiae.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kruckenhauser et al (2011) estimated a split below 1 Myr between the two forms of G. barreimiae, and their experiments indicate that the sequences of the cytb gene used by Colli et al (2008) may be derived partly from the functional cytb gene and partly from nuclear pseudogenes (numts (copies of mitochondrial genes that have been translocated into the nuclear genome)). For this reason, in the present study we resequenced the cytb gene in both G. barreimiae and P. andruzzii cavefish and analyzed this together with cytb sequences from an additional 146 species ( Supplementary Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, os troglóbios são bons modelos no estudo micro-e macroevolutivo e tem sido estudados de forma crescente na perspectiva filogeográfica (STRECKER, et al, 2003;2004;NIEMILLER et al, 2008;JUAN et al, 2010;COLLI et al, 2009;CHIARI et al, 2012). No Brasil, estudos sobre a fauna subterrânea nesta perspectiva encontram-se em desenvolvimento inicial.…”
Section: Conclusõesunclassified